قواعــد العرف الفقهية عند بن قيم الجوزية - Mahasin Zuhair Thaher; Abedllah Ali Alsafee (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This research raises the subject of fiqh rules regarding customs according to Ibn Qayyim al-Jauziyyah with the aim of revealing the current fiqh rules regarding customs according to Ibn al-Qayyim, mentioning the implementation of these rules in fiqh matters, and determining in what fields of jurisprudence these rules can be implemented. This research uses inductive, analytical, and applied approaches. The research results show several things. First, the disclosure of the main rules regarding customs, which were considered final by Ibn al-Qayyim in his ijtihad, and in general, there are three rules, namely: the rule